Environmental influences on the daytime vertical distribution of Cape hakes and implications for demersal trawl estimates of hake abundance off the west coast of South Africa - Maree, R C (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2000)
The demersal fishery off the west coast of South Africa experiences decreased catches per unit effort of hake, Merluccius capensis and M. paradoxus, following the onset of strong south easterly winds. Research has demonstrated that, during daylight hours, Cape hakes migrate vertically in the water column in response to strong south easterly winds, decreasing their availability to the bottom trawl. Hydroacoustic, trawl and environmental data were collected off the West Coast during both calm and wind-swept periods in an attempt to understand the forces that initiate this behaviour, its spatial variability and the implications for demersal trawl estimates of abundance. Near-bottom currents appear to be the primary factor influencing the vertical distribution of the demersal fish community, of which hake constitutes a large proportion, during daylight hours. Correlation between wind and near-bottom currents suggest that the poleward component of the currents increase in velocity within eight hours following the onset of south easterly winds. The fish avoid boundary layers where currents change direction and speed dramatically, and seem to concentrate in waters with relatively stable current regimes. This result questions the assumption of CPUE-based assessment models that hake availability to the bottom trawl is constant or varies randomly. The incorporation of acoustic assessment techniques to demersal surveys has potential, but may be most valuable by supplementing swept-area estimates of abundance, since the sampling efficiency of these methods varies within the water column. The incorporation of wind indices and gear performance data to Cape hake assessment models have been identified as useful considerations for the future.
Keywords: Hake; Fisheries -- Environmental aspects -- South Africa; Fisheries -- South Africa; Trawls and trawling